2017
DOI: 10.1126/sciadv.1602026
|View full text |Cite|
|
Sign up to set email alerts
|

Coordinated infraslow neural and cardiac oscillations mark fragility and offline periods in mammalian sleep

Abstract: Mammalian sleep alternates between sensory-responsive and protected offline periods via coordinated neural and cardiac rhythms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
299
2
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 178 publications
(339 citation statements)
references
References 54 publications
(81 reference statements)
37
299
2
1
Order By: Relevance
“…At ISL>5 s, the reduced spindle likelihood (right side of Fig 2F) may reflect the initial shift to a sleep state not conducive to spindles. Additionally, we found a strong peak at an infraslow frequency (~0.02 Hz; Fig 2B), in line with a recent report suggesting the presence of spindle-rich intervals separated by ~50 s (27). Our findings therefore underscore the importance of considering spindles on the meso-scale (~0.2-0.3 Hz), intermediate between the sub-second scale of the oscillations themselves (11)(12)(13)(14)(15)(16) and the infra-slow scale just under a minute (0.02 Hz).…”
supporting
confidence: 93%
“…At ISL>5 s, the reduced spindle likelihood (right side of Fig 2F) may reflect the initial shift to a sleep state not conducive to spindles. Additionally, we found a strong peak at an infraslow frequency (~0.02 Hz; Fig 2B), in line with a recent report suggesting the presence of spindle-rich intervals separated by ~50 s (27). Our findings therefore underscore the importance of considering spindles on the meso-scale (~0.2-0.3 Hz), intermediate between the sub-second scale of the oscillations themselves (11)(12)(13)(14)(15)(16) and the infra-slow scale just under a minute (0.02 Hz).…”
supporting
confidence: 93%
“…However, the average duration of SWA reactivation in CAP was reported as 12.66 s which is longer than our ACE observations. Lecci et al 34 found periodic sigma activity (but not SWA) that was more prevalent in Stage 2 sleep than SWS and associated with memory consolidation in a declarative task (human) as well as hippocampal ripple activity (in mice). The present results, on the other hand, identified a heretofore undescribed burst in HR activity, that correlated with prominent, aperiodic, ACE-related increases in SWA and sigma, as well as parasympathetic activity, that predicted gains in declarative memory during Stage 2 and SWS.…”
Section: Discussionmentioning
confidence: 99%
“…However, several neural processes occur over much longer timescales (Huk et al, 2018). Transitions between sleep and wakefulness and between different stages of sleep occur on timescales of minutes and hours (Weber and Dan, 2016;Lecci et al, 2017;Meisel et al, 2017). During wakefulness, changes in arousal can span tens of seconds and minutes, yet they affect performance in sub-second behavioural tasks (Harris and Thiele, 2011;Palva and Palva, 2012;McGinley et al, 2015).…”
Section: Introductionmentioning
confidence: 99%